2021
DOI: 10.1097/md.0000000000027067
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of corticosteroid injection and splint in diabetic de Quervain's tenosynovitis patients

Abstract: Background: There is no clear information on the efficacy of corticosteroids, and splints in the treatment of patients with diabetes mellitus (DM). The aim of this study was to compare the outcomes of isolated corticosteroid injection therapy with splint treatment with corticosteroid injection in patients with and without DM. Methods: 84 diabetics, and 84 healthy patients with a diagnosis of de Quervain's tenosynovitis were included in our study. The patients were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Among 4 studies in this meta-analysis; 1 was of high overall ROB and 3 were of some concerns of ROB. Postinjection immobilization was for either 3 weeks or 4 weeks, in a cast, a splint, or either .…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Among 4 studies in this meta-analysis; 1 was of high overall ROB and 3 were of some concerns of ROB. Postinjection immobilization was for either 3 weeks or 4 weeks, in a cast, a splint, or either .…”
Section: Resultsmentioning
confidence: 88%
“…A total of 37 studies were initially found to be eligible. Of those, 7 studies did not include 1 of our predefined outcome measures or included patients with conditions other than DQT and did not analyze data separately and were therefore excluded (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of corticosteroids as a treatment for de Quervain's tenosynovitis is positive in both diabetics and healthy people, however it is less effective in diabetics (13).…”
Section: Developmentmentioning
confidence: 99%